Academic pediatric clinical research: factors associated with study implementation duration. Issue 1 (December 2016) - Meier-Girard, Delphine; Tibi, Annick; Abdoul, Hendy; Prot-Labarthe, Sonia; Brion, Françoise; Bourdon, Olivier; Alberti, Corinne
Abstract Background The ethical, methodological, and technical aspects of pediatric research, often results in complications and delays in implementation. Our objective was to identify factors associated with the implementation duration of hospital-based pediatric studies. Methods All hospital-based pediatric studies sponsored by AP-HP between 2002 and 2008 were retrospectively identified. Association of the funding mechanism and methodological factors with the implementation duration was assessed using a multivariable mixed linear model. Pharmaceutical factors were explored as part of a subgroup analysis restricted to the studies involving drug therapy. Given that we took an exploratory approach, factors associated with implementation duration withp < 0.10 were kept in the final models. Results A total of 139 studies were evaluated. The median implementation duration was 17.1 months (range: 0.9-55.3 months), and tended to increase over time (from 14.9 [25th percentile-75th percentile: 11.5-19.9] months in 2002 to 23.7 [15.2-31.0] months in 2008, p = 0.01). External (coefficient [95 % confidence interval]: -7.7 [-11.9;-3.5] months, p < 0.001) and internal funding (-5.395 % CI [-9.8;-0.8], p = 0.02) compared to governmental funding and number of centers (-0.195 % CI [-0.2;0.02] months for 1 center increase, p = 0.07) were associated with reduced duration, whereas interventional study (either involving drug therapy (6.095 % CI [0.7;11.3] months, p = 0.03 or not (3.595 % CI [-0.3;7.3] months, p = 0.06) was associated with increased duration compared to observational study. Regarding the 35 studies involving drug therapy, external funding decreased duration (-6.795 % CI [-13.2;-0.2] months, p = 0.05), whereas studies involving solely a pediatric population (7.895 % CI [1.1;14.5] months, p = 0.01) (compared to mixed adult-pediatric population), a placebo-controlled design (6.695 % CI [0.9;12.3] months, p = 0.01), and inappropriate drug formulation for at least one drug used in the study (6.995 % CI [-0.2;14.0] months, p = 0.06) were associated with increased duration. Conclusion Implementation of hospital-based pediatric studies primarily faced delays when they were interventional and, in particular, when they involved drug therapy. Regarding the latter, difficulties that resulted in delayed studies arose with respect to the supply of drugs and placebo in age-appropriate dosages and route of administration. Therefore, difficulties related to the use of pharmaceuticals need to be anticipated earlier in order to avoid implementation delays.